Rancang Bangun Sistem Informasi Customer Loyalty untuk Keunggulan Kompetitif Organisasi - Mulyani, Sri; Mustafid, Mustafid; Widodo, Catur Edi (Universitas Diponegoro, 2012)
Utilization of information technology to achieve competitive advantage has become a necessity for business people and managers of organizations in the information age now. This research aim to create a customer loyalty that the information system is one part of theCustomer Relationship Management to collect data on indicators of customer loyalty. Indicator of customer loyalty is determined according empirical model customer loyalty and create customer loyalty information system that can be used to gain competitive advantage organizations. Structural Equation Modeling is used to obtain indicators of customer loyalty. Customer loyalty info rmation system designed using prototype system development and modeling analysis using Data Flow Diagram, database design using Entity Relationship Diagram, and a web-based interface. Web-based information systems that provide online customer survey facilities and analysis results in the form of customer loyalty index values shaped by the dynamic graphic indicator of loyalty according to the empirical study of customer loyalty that can be used to gain competitive advantage. The value of customer loyalty index cons ists of four main variables, namely: the ability to anticipate customer value, customer value anticipation peace, customer satisfaction, and loyalty.Keywords: Customer loyalty, Structural Equation Modeling, Index loyalty, Competitive advantage